IMPLEMENTING MEDIA OF COMPUTER-BASED TEST FOR ENGLISH LANGUAGE PROFICIENCY OF VOCATIONAL HIGH SCHOOL STUDENTS AT THE BORDERLINE BETWEEN INDONESIA AND TIMOR LESTE - Yohanes Adio Balan; Djuniadi Djuniadi (Prosiding Seminar Nasional IPTEK Terapan (SENIT) 2016 Pengembangan Sumber Daya Lokal Berbasis IPTEK, 2016)
Research about “Implementing Media of Computer-Based Test for English Language Proficiency of West Timorese Vocational High School Students” is aimed to answer the question whether or not the use of computer-based test effective and practical as the models of test instrument for English language proficiency test of vocational high school students. It is a research and development (R and D) referred to Borg and Gall model (1989). The research took place at the borderline between Indonesia and Timor Leste, which covers three vocational high schools: SMKN 1 Kefamenanu, SMK Katolik Kefamenanu and SMK Intan Grafika Kefamenanu. Software of Wonder share Quiz creator is used to produce a model of computer-based test. The questions are chosen from standardized questions of national examination based on competency standard of the second grade students of SMK. Each single question appears on computer screen, and the students are to answer by doing a click on the correct options. Validation was done to measure the quality of the computer-based test media, the effectiveness and the practicability of the CBT. The products and instruments are validated by expertise valuator of lecturers and teachers. The first validation came up with an unsatisfactory result, in which the indicators had not met the criteria or standards. After the revision, the second validations was conducted, the indicators had met the criteria or standards. The media of computer-based test and the practicability of the CBT are Valid. Key words: Computer-Based Test; E-learning; English proficiency